Fast Modeling of Large Wave Energy Farms Using Interaction Distance Cut-Off - Malin Göteman; Jens Engström; Mikael Eriksson; Jan Isberg (Energies, 2015)
In many wave energy concepts, power output in the MW range requires the simultaneous operation of many wave energy converters. In particular, this is true for small point-absorbers, where a wave energy farm may contain several hundred devices. The total performance of the farm is affected by the hydrodynamic interactions between the individual devices, and reliable tools that can model full farms are needed to study power output and find optimal design parameters. This paper presents a novel method to model the hydrodynamic interactions and power output of very large wave energy farms. The method is based on analytical multiple scattering theory and uses time series of irregular wave amplitudes to compute the instantaneous power of each device. An interaction distance cut-off is introduced to improve the computational cost with acceptable accuracy. As an application of the method, wave energy farms with over 100 devices are studied in the MW range using one month of wave data measured at an off-shore site.